An anthropological approach to a transitional issue – analysis of the autonomy required from mathematics students in the French lycee - Castela, Corine (NOMAD Nordic Studies in Mathematics Education, 2009)
This paper intends to contribute to the process of theoretical networking within the mathematics education research community. Some key elements of the Anthropological Theory of Didactics are recalled and used to deal with the issue of French students’ transitional difficulties in mathematics between Collège (lower secondary school) and Lycée (upper secondary school). The intention is showing how this theoretical framework, in contrast with a theoretical framework of Advanced Mathematical Thinking, provides tools to analyse the changes between these two institutions and thus supports the following assumption: An increasing autonomy as problem solvers as well as mathematics learners is required from the upper secondary school students. This hypothesis led to a clinical investigation on high school students’ homework. This paper addresses the hypothesis by drawing on the case of three high-achieving students.